2017
DOI: 10.7554/elife.26464.023
|View full text |Cite
|
Sign up to set email alerts
|

Author response: Loss of adult skeletal muscle stem cells drives age-related neuromuscular junction degeneration

Abstract: Neuromuscular junction degeneration is a prominent aspect of sarcopenia, the ageassociated loss of skeletal muscle integrity. Previously, we showed that muscle stem cells activate and contribute to mouse neuromuscular junction regeneration in response to denervation (Liu et al., 2015). Here, we examined gene expression profiles and neuromuscular junction integrity in aged mouse muscles, and unexpectedly found limited denervation despite a high level of degenerated neuromuscular junctions. Instead, degenerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…After further screening of remaining articles, 49 were excluded, in which 23 had no comparisons among different ages, 20 were review papers 4 were conference reports and 2 had no full text access. Therefore, 30 manuscripts were included for the systematic review (Courtney and Steinbach, 1981;Banker et al, 1983;Oda, 1984;Herscovich and Gershon, 1987;Smith and Chapman, 1987;Anis and Robbins, 1988;Smith et al, 1990;Prakash and Sieck, 1998;Connor et al, 2002;Deschenes and Wilson, 2003;Apel et al, 2009;Mcmullen and Andrade, 2009;Suzuki et al, 2009;Kulakowski et al, 2011;Li et al, 2011;Samuel et al, 2012;Cheng et al, 2013;Deschenes et al, 2013;Personius and Parker, 2013;Aare et al, 2016;Willadt et al, 2016;Xie et al, 2016Xie et al, , 2018Hughes et al, 2017;Liu et al, 2017;Snyder-Warwick et al, 2018;Zhao et al, 2018;Soendenbroe et al, 2019Soendenbroe et al, , 2020Uchitomi et al, 2019). The flow chart presenting the selection process is shown in Figure 1.…”
Section: Results Of the Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…After further screening of remaining articles, 49 were excluded, in which 23 had no comparisons among different ages, 20 were review papers 4 were conference reports and 2 had no full text access. Therefore, 30 manuscripts were included for the systematic review (Courtney and Steinbach, 1981;Banker et al, 1983;Oda, 1984;Herscovich and Gershon, 1987;Smith and Chapman, 1987;Anis and Robbins, 1988;Smith et al, 1990;Prakash and Sieck, 1998;Connor et al, 2002;Deschenes and Wilson, 2003;Apel et al, 2009;Mcmullen and Andrade, 2009;Suzuki et al, 2009;Kulakowski et al, 2011;Li et al, 2011;Samuel et al, 2012;Cheng et al, 2013;Deschenes et al, 2013;Personius and Parker, 2013;Aare et al, 2016;Willadt et al, 2016;Xie et al, 2016Xie et al, , 2018Hughes et al, 2017;Liu et al, 2017;Snyder-Warwick et al, 2018;Zhao et al, 2018;Soendenbroe et al, 2019Soendenbroe et al, , 2020Uchitomi et al, 2019). The flow chart presenting the selection process is shown in Figure 1.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…The 30 selected studies were conducted from 1981 to 2020: 14 rat studies (Courtney and Steinbach, 1981;Smith and Chapman, 1987;Smith et al, 1990;Prakash and Sieck, 1998;Connor et al, 2002;Deschenes and Wilson, 2003;Apel et al, 2009;Mcmullen and Andrade, 2009;Suzuki et al, 2009;Deschenes et al, 2013;Aare et al, 2016;Xie et al, 2016Xie et al, , 2018Hughes et al, 2017), 13 mouse studies (Banker et al, 1983;Herscovich and Gershon, 1987;Anis and Robbins, 1988;Kulakowski et al, 2011;Li et al, 2011;Samuel et al, 2012;Cheng et al, 2013;Personius and Parker, 2013;Willadt et al, 2016;Liu et al, 2017;Snyder-Warwick et al, 2018;Zhao et al, 2018;Uchitomi et al, 2019) and 3 human studies (Oda, 1984;Soendenbroe et al, 2019Soendenbroe et al, , 2020. The characteristics of the included studies are shown in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations